Discourse Strategies in Selected African Suicide Notes - Sanni, Oluwole (AUC Knowledge Fountain, 2021)
The present study aims to investigate the discourse strategies, positioning moves, and sociological variables that characterized the selected African suicide notes. Twenty suicide notes from different African countries constituted the data for the study. The data was deductively analysed using Davis & Harre (1999) positioning theory aside being inductively analysed. The results concluded that the discourse and structural patterns of metaphor, intertextuality, pronouns, presupposition, repetition, if conditionals, and intensifiers were deployed by the African suicide completers to demonstrate agency or/and victimhood. Also, first-order, second-order, third-order, expert and moral positioning were used in the suicide notes for self and other portrayer of the suicide completers and specific audience(s). More so, the social variables or religion, sexuality, and family influences African suicide constructions and unearth how the African context provide insights in the understanding of suicidal behaviour. This study has ultimately contributed to the dearth of studies on African suicide notes and proven that suicide texts are viable instances of language use with linguistic meanings and metalinguistic significance. Furthermore, the study has demonstrated that the African context has added rich perspectives to suicide notes studies with illuminating understanding of the inherent messages of suicide completers.